METODE INTERNALISASI NILAI-NILAI KARAKTER DALAM KELUARGA SANTRI, PEDAGANG DAN GURU - Rofikasari Mutmainah; Jumari (EL-Islam, 2019)
This article examines the important role of families in character education. Family as the first and foremost place for a child to get an education. In this study discussed the character values instilled in santri families, traders and teachers as well as methods of internalizing character values used in the families of santri, traders and teachers. By using a phenomenological qualitative approach based on observations, interviews and documentation with qualitative descriptive analysis techniques and checking the validity of triangulation data. The results of this study in the form of character values that are instilled in the santri familyinclude religion, honesty, discipline, caring, courtesy, responsibility and patience. In the merchant family include honesty, cooperation, respect for time, being patient, praying or religious, creative and disciplined. In the teacher's family includes honest, disciplined, religious, independent, caring for the environment, intellectuals, morals, confidence, and achievement. The method of internalizing character values used in applying these characters is the method of habituation, exemplary, implementation, advice, stories and affection.